TRAINING ON WEAVING TECHNIQUES, DESIGN AND MARKETING STRATEGIES TO DEVELOP EXPORT POTENTIAL ON INDONESIA BAMBOO CRAFT - Hidayat, July; Pramono, Rudy; Juliana, Juliana; Hubner, Ira B.; Dharmawan, Cherry (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Bamboo is an endemic plant in Indonesia. Of the 1439 types of bamboo in the world, 162 are in Indonesia. Bamboo has a crucial role in balancing the ecosystem. It reduces the greenhouse effect. Bamboo forests play a role in absorbing CO2 and converting CO2 into carbon stored in trees. Bamboo is a natural material in the craft industry with great economic potential. It doesn’t damage the environment, has a fast production period, and multi-functional. Those traits make it suitable for developing green economy programs. When modern society consumes traditional bamboo crafts, earnest improvements in the design aspect, production quality related to the technology for making bamboo crafts, and aspects of publication or marketing of Indonesian bamboo are required. Sahabat Bambu Batik and Dunia Bambu Sukabumi are local bamboo craftsmen communities. The problem for the craftsmen is the need for appropriate technology, marketing, and capital. For this reason, in collaboration with the craftsman communities, craft industry, government, and the Beppu bamboo craft school in Tokyo, UPH provides training in Japanese bamboo craft techniques, design, and marketing strategies. The Japanese craftsman teach the craft techniques that enable precise bamboo crafts with a standardized production process to compete in the international market.